2022
DOI: 10.1371/journal.pgph.0000485
|View full text |Cite
|
Sign up to set email alerts
|

Community mask wearing as a COVID-19 preventive measure, its barriers, and motivators among rural households of Uganda: A mixed methods approach

Abstract: Adherence to mask wearing has the potential to reduce coronavirus disease 2019 acquisition risk. However, there is limited information about community mask wearing and its predictors among rural populations. This study aimed to assess the level of adherence to community mask wearing as a COVID-19 prevention measure, its barriers, and motivators among the Ugandan rural population of Wakiso District. This cross-sectional study utilised both quantitative and qualitative data collection methods. The quantitative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Regarding intrapersonal impeding factors, consistent with previous studies, 2123 perceived physical and social interaction barriers when wearing a mask were reported by participants from all 4 countries. Individual-level interventions can be introduced to educate people on how to conquer these barriers.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding intrapersonal impeding factors, consistent with previous studies, 2123 perceived physical and social interaction barriers when wearing a mask were reported by participants from all 4 countries. Individual-level interventions can be introduced to educate people on how to conquer these barriers.…”
Section: Discussionsupporting
confidence: 89%
“…A survey based on 708 Malaysian adults also demonstrated that the prevalence of wearing a face mask outside while it was not mandatory was 66.0% [ 27 ]. Several studies in Uganda reported that mask-wearing prevalence in rural communities ranged from approximately 33.0 to 70.3% in the later phase of the COVID-19 pandemic [ 2 , 28 ]. Furthermore, the study in Uganda, similar to ours, revealed that knowledge of mask-wearing as a COVID-19 prevention measure was positively associated with mask-wearing adherence [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the COVID-19 pandemic, face masks have played a vital role globally in preventing the spread of the disease [ 1 ]. Epidemiologic evidence demonstrates that mask use is 50 to 70% effective in preventing the spread of COVID-19 within a community [ 2 ]. Furthermore, surgical masks are known to inhibit PM2.5, which is a major health-related problem in Thailand [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the police officers were accepting bribes and allowing those who flouted COVID-19 measures to go scot-free was also reiterated by the General Commissioner of police when he appeared before the Health and Child Care Parliamentary Portfolio Committee in June 2020 (Mutanda, 2022). Non-compliance to face masking is also prevalent in Uganda and they also had to use law enforcement agents to promote compliance (Lubenga, et al 2022). Paradoxically, the law enforcement agents who are supposed to police people also violate the COVID-19 protocols by not wearing face masks and practicing social distancing (Maulani, Nyadera & Wandeka, 2021).…”
Section: Socio-economic Factors and The Non-compliance Of Face Masksmentioning
confidence: 99%